Effects of Social Media Marketing on Vegetarian Food Literacy and Post-Purchase Decision - Sherwin, Nadya Sherwin; Helmi, Sulaiman; Gunarto, Muji; Trisninawati, Trisninawati (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2024)
This study aims to determine and analyze the effect of social media on vegetarian food literacy, the effect of vegetarian food literacy on purchasing decisions, and the components of the AISAS model that most effectively influence consumer purchasing decisions. This study involved 158 respondents. Respondents consisted of Generation Y and Z in Palembang, who were selected using the purposive sampling quota technique. Data collection was carried out using an online questionnaire. SEM-PLS analysis in this study was used to analyze the direct influence of social media on vegetarian food literacy and consumer purchasing decisions based on AISAS modeling. The results of this study indicate that social media has a significant and positive effect on consumers' attention, interest, and search factors. The share factor is the most influential factor in consumer purchasing decisions and on vegetarian products. The influence given by influencer testimonials and friends is considered the most effective in attracting other consumers to buy. This can be a reference for vegetarian food businesses to find the most effective marketing methods to attract consumer purchasing decisions